A Lesson in Standardization – Subtle Aspects of the Processing of Samples Can Greatly Affect Dogs' Learning - Guest, Claire M.; Harris, Rob; Anjum, Iqbal; Concha, Astrid R.; Rooney, Nicola J. (Frontiers in Veterinary Science, 2020)
Training new medical odours presents challenges in procuring sufficient target samples, and suitably matched controls. Organisations are often forced to choose between using fewer samples and risking dogs learning individuals or using differently sourced samples. Even when aiming to standardise all aspects of collection, processing, storage and presentation, this risks there being subtle differences which dogs use to discriminate, leading to artificially high performance, not replicable when novel samples are presented. We describe lessons learnt during early training of dogs to detect prostate cancer from urine. Initially, six dogs were trained to discriminate between hospital-sourced target and externally sourced controls believed to be processed and stored the same way. Dogs performed well: mean sensitivity 93.5% (92.2-94.5) and specificity 87.9% (78.2-91.9). When training progressed to include hospital-sourced controls, dogs greatly decreased in specificity 67.3% (43.2-83.3). Alerted to a potential issue, we carried out a methodical, investigation. We presented new strategically chosen samples to dogs and conducted a logistic regression analysis to ascertain which factor most affected specificity. We discovered the two sets of samples varied in a critical aspect, hospital-processed samples were tested by dipping the urinalysis stick into the sample, whilst for externally sourced samples a small amount of urine was poured onto the stick. Dogs had learnt to distinguish target aided by the odour of this stick. This highlights the importance of considering every aspect of sample processing even when using urine, often believed to be less susceptible to contamination than media like breath.